Oxygen Gas Vacuum Plasma Treatment on PVA/Chitosan/HAp Scaffold Nanofiber - Nada Shofura Faradyana; Maulia Ingganis Wuriantika; Muhammad Nurhuda; Masruroh Masruroh; Dionysius Joseph Djoko Herry Santjojo; Norhayati Ahmad; Hartatiek Hartatiek; Yudyanto Yudyanto (Universitas Negeri Malang, 2022)
Scaffold in the form of nanofibers in bone tissue engineering applications continues to be developed. In this study, nanofibers are composed of PVA/CS/HAp with characteristics that can support medical applications such as bone tissue engineering. Vacuum plasma treatment was carried out to modify the nanofiber surface. The results of the morphological analysis showed that the vacuum plasma treatment of oxygen gas caused the surface of the PVA/CS/HAp nanofibers to become rougher with a change in diameter. Before the oxygen gas vacuum plasma treatment, the diameter of the nanofiber had a range of 83–365 nm. After the oxygen gas vacuum plasma treatment, the diameter had a size range of 105–293 nm. Furthermore, the vacuum plasma treatment carried out showed increased hydrophilic properties. The average contact angle values before and after oxygen gas vacuum plasma treatment were (39.0 ± 0.0005)° and (10.3 ± 0.0005)°, respectively.DOI: 10.17977/um024v7i22022p108